Effect of accentuated eccentric loading countermovement jumps and drop jump training with ladder training versus ladder training alone on sprint performance and change of direction ability in futsal players: A randomized controlled trial protocol - Darpan Chaudhari; Swapnil U. Ramteke (PLoS ONE, 2026)
Futsal is a fast-paced, high-intensity 5-a-side sport that demands rapid sprints and frequent changes of direction (COD), critical for match performance. While ladder training is known to enhance agility and coordination, combined effects of accentuated eccentric loading (AEL), countermovement jumps (CMJ), and drop jumps (DJ) increase lower body power, it is unclear how these exercises work together to produce futsal-specific results. This paper presents the study protocol for a randomized controlled trial investigating the impact of AEL CMJ, DJ, and ladder training on sprint and COD performance in futsal players. This 6-week, parallel, single-blinded randomized controlled trial, in which outcome assessor will be blinded to group allocation. A total of 62 recreational and competitive futsal players (aged 18–30 years) from futsal turfs across Sawangi Meghe, Wardha. Participants will be randomized (1:1) to receive AEL CMJ, DJ, and ladder training or ladder training alone, 3 times per week. The primary outcomes are the between-group differences in sprint performance (30-meter Sprint Test) and COD ability (Agility T-Test) from baseline to post-intervention (week 6). In order to compare changes between time points and groups, Primary analysis will be conducted using linear mixed-effects models with participant-level random intercepts, following the intention-to-treat principle (CTRI/2025/04/085611).